The caller - Fossum, Karin, 1954- (Fossum, Karin, 1954- Inspector Sejer mystery., 2012)
Inspector Sejer investigates the delivery of a threatening postcard that coincides with the discovery of a child who was found covered in blood but unharmed in her stroller.